Inovação de processo : proposta de aprimoramento do sistema de avaliação dos impactos de tecnologias geradas pela Embrapa - Parapinski, Lucia Maria (2023)
The AMBITEC-AGRO methodology is used for multidimensional evaluation of the economic, social and environmental impacts resulting from the technologies developed by Embrapa. In addition, its indicators make it possible to draw up the Social Balance Sheet as an account to society. However, the evaluation process faces complex challenges, such as adaptation to different technologies, financial limitations, lack of multidisciplinary teams and subjective elements. In this context, this study sought to identify the requirements needed to improve this process, from the perspective of the Focal Point representatives of the evaluation process at each of Embrapa's 43 Decentralized Units. The research adopted a mixed approach (quantitativequalitative), characterized as applied, descriptive, using methods such as bibliographic and documentary research, case study, field survey; participation in meetings and systematic observations during the monitoring of the process of evaluating the impacts of the BRS Anahí cultivar on sesame production in the 2021/2022 harvest in CanaranaMT. The results were analyzed using the data triangulation technique, MaxQda software and the SWOT and GUT matrices. The results of the research showed that the process has been consolidated in the DUs, however, some essential requirements for adjustments were identified, such as the need for: training, capacity building and training of evaluation teams; financial resources; making the methodology more flexible and simpler; promoting events between the DUs to exchange experiences; improving coordination between rural extension and agents/adopters; legal support for sharing information; quantitative criteria; issues related to family farming and environmental sustainability. In short, although the evaluation process is institutionalized, the study highlights the importance of making the necessary adjustments in order to strengthen credibility, increase user satisfaction and improve decision-making.